FORMULATION OF CIVIL LIABILITY MODEL IN ARTIFICIAL INTELLEGENCY ECOSYSTEM : INTEGRATION OF THE PRINCIPLES OF STICT LIABILITY AND FAULT LIABILITY IN INDONESIAN CIVIL LAW - Erwin Syah; Fero Sanjaya; Herlita Eryke (SOSIOEDUKASI, 2026)
The rapid development of Artificial Intelligence (AI) within the digital ecosystem has introduced new complexities in civil law relationships in Indonesia, particularly regarding liability for damages caused by algorithm-based systems. This study aims to analyze the normative weaknesses of civil liability regulations in Indonesian positive law and to formulate a liability model that is adaptive to the characteristics of AI. This research employs a normative legal method with statutory, conceptual, and comparative approaches. The findings reveal that the fault liability principle under Article 1365 of the Indonesian Civil Code is no longer adequate due to the difficulty of proving fault in autonomous and black box AI systems. The disharmony between the Civil Code, the Electronic Information and Transactions Law, and the Personal Data Protection Law further highlights the existence of a legal vacuum. Empirical data indicates a significant increase in data breaches and cybercrime cases over the past 3–5 years, affecting civil rights. This study proposes the “Hybrid Liability AI” model, integrating fault liability and strict liability based on a risk-based approach. The model enables proportional allocation of liability among developers, operators, and users. The application of strict liability to high-risk AI systems ensures effective victim protection, while fault liability maintains fairness within the legal system. This research contributes theoretically to the development of civil liability doctrine and provides practical recommendations for AI regulatory frameworks in Indonesia. KEYWORDS: Artificial Intelligence, Civil liability, Fault liability, Strict liability, Hybrid liability